Three new species of genus Mecopoda Serville, 1831 from China (Orthoptera: Tettigoniidae: Mecopodinae) - Liu, Yun-Fei; Shen, Chu-Ze; Gong, Pu; Zhang, Ling; He, Zhu-Qing (Zootaxa, 2019)
Only six species or subspecies of genus Mecopoda have been recorded with two species recorded from China prior to this study. We describe 3 new species, M. hainanensis He sp. nov., M. fallax He sp. nov. and M. marmorata He sp. nov. from Yunnan and Hainan. Although M. hainanensis is similar to M. niponensis, M. fallax is similar to M. elongata elongata, their songs can be used for identification. The result of molecular study also supports the validity of three new species. The type specimens are deposited in Museum of Biology, East China Normal University (ECNU).